Kemampuan Pemecahan Masalah Siswa Kelas XI Dalam Menyelesaikan Soal Matriks Ditinjau dari Self-efficacy - Wardatul Laili; Ucik Fitri Handayani (Kilau Publishing, 2025)
This study aims to describe students' problem-solving abilities in solving matrix problems in terms of their self-efficacy levels. The study used a descriptive qualitative approach with three eleventh-grade students representing high, medium, and low self-efficacy categories as subjects. Questionnaires, tests of problem-solving ability, and in-depth interviews were used to gather data. Students who scored higher on the self-efficacy measure were more likely to systematically complete each of the four steps of problem-solving: identifying the issue, developing a plan of action, carrying out the plan, and finally, evaluating the outcomes. Even though they were less confident and accurate, students with medium self-efficacy nonetheless proceeded through all the steps. Students who lacked confidence in their abilities could only complete one level and often struggled to find solutions to issues. These results show that students' mathematical problem-solving skills are significantly impacted by their degree of self-efficacy. Thus, it is essential that mathematics learning methodologies prioritise the cultivation of self-efficacy, particularly when dealing with intricate topics like matrices.